Founding family and auditor choice: Evidence from Taiwan - Hsu, Hwa‐Hsien; Lin, Che‐Hung; Tsao, Shou‐Min (Corporate governance : an international review, 2018)
Manuscript Type Empirical Research Question/Issue From an agency perspective, we investigate whether family ownership and control configurations are systematically associated with a firm's choice of auditor. Our analysis focuses on three different characteristics of family ownership and control: family ownership (cash flow rights), disparity between cash flow and voting rights held by family owners (cash–vote divergence), and the family identities of CEOs. Research Findings/Insights Our findings suggest that different family ownership and control configurations lead to different agency effects. The alignment effect prevails in family firms with greater family ownership, founder CEOs, and professional CEOs, whereas the entrenchment effect prevails when there is greater cash–vote divergence. Despite the presence of two distinct types of agency effects, regardless of differences in family ownership and control configurations, none of these firms is inclined to appoint higher‐quality auditors. Theoretical/Academic Implications This study advances our understanding of the varied agency effects arising from family ownership, cash–vote divergence, and the family identities of CEOs, as well as the impact of family ownership and control features on auditor choice. Our empirical evidence provides a unique insight, showing that higher‐quality auditors do not tend to be appointed in firms where family alignment with outside investors is relatively strong, as this lowers demand for such auditors. In addition, although family entrenchment may create greater outside investor demand for higher‐quality auditors, such demand is difficult to realize. Practitioner/Policy Implications Auditors are an important external governance mechanism. This study offers insights for policymakers, family owners, auditors, and other capital market participants, with regard to the varied effects of different family ownership and control features on auditor choice.